Structural and corrosion protection analyses of coatings containing silicone-polyester resins - Ramesh, K.; Osman, Z.; Arof, Abdul Kariem; Vengadaeswaran, B.; Basirun, Wan Jefrey (Emerald, 2008)
Purpose - Silicone and polyester resins have been prepared at various compositions with the purpose of determining the best performing binder system. The coating materials that have been developed have been analysed and evaluated for their protection ability. Design/methodology/approach - Silicone and polyester resins have been prepared at various compositions to identify best performing binder system. To evaluate the properties, different analytical methods have been employed. Fourier transform infrared spectroscopy has been utilised to study the chemical changes when the polymers were mixed together. Corrosion resistance has been tested through potential time measurement test using NaCl solution. The surface morphology has been evaluated using scanning electron microscopy/energy dispersive X-ray (EDX) analysis. Findings - There is a change in intensity of the peaks and shift in the peak values of the functional groups observed. Scanning electron microscopy graphs show the uniform surface morphology of the systems developed. From the EDX analysis, the composition of the coating material has been found. The results showed that the coatings could protect the substrate for 30 days of immersion in 3 per cent NaCl electrolyte solution. Originality/value - The paper provides an analysis of coatings containing silicone-polyester resins.